How informed should be informed consent? - Nazli Hossain (Journal of the Pakistan Medical Association, 2025)
Informed consent is an important part of not only surgicalprocedure, but also any physical examination. Health careworkers are expected to observe the boundaries set bythe different medical and ethical bodies in theirrespective fields. The Good Clinical practice is that theSurgeon knows the procedure thoroughly, is able to givecomplete information about it, is able to reach a mutualdecision about the treatment and respect the decisionand trust of the patient. Here we describe a case, wherebreach in observing these practice guidelines resulted inactivation of the legal framework with seriousconsequences for the health care professional. Continue...